Assessment of Brush Biopsy Findings and Salivary LDH Levels in Oral Mucosal Lesions of Tobacco Users - Sam P. Davidson; Senthil Kumar; Elangovan Somasundaram; Suman Jaishankar (Indian Journal of Dental Research)
Introduction: The oral brush cytology is an alternative method developed to improve the efficacy of conventional cytology in oral potentially malignant disorder (OPMD), and salivary lactate dehydrogenase (LDH) which is a cytoplasmic enzyme has been widely used as a marker for diagnosing various diseases. The purpose of the study is to evaluate the brush biopsy findings and salivary LDH levels for the early diagnosis of premalignant and malignant lesions of the oral cavity. Materials and Methods: Patients with deleterious habits including tobacco-related lesions such as leukoplakia, tobacco pouch keratosis, and oral cancer were included in the study. For each patient, saliva sample was collected, brush biopsy was done and smears were prepared. Collected saliva samples were analysed for salivary LDH levels and prepared smears were analysed for dysplastic changes and statistical analysis was performed. Results: Out of 80 samples, 30 were leukoplakia, 45 were tobacco pouch keratosis and 5 were oral cancer, and 13 samples showed positive dysplastic changes, 26 samples showed atypical dysplastic changes and 41 samples showed no signs of dysplastic changes and concluded as negative. On comparing the results of brush biopsy findings and salivary LDH levels, the mean salivary LDH value for positive dysplasia was elevated and the P value was statistically significant (P value: 0.00). Conclusion: Brush biopsy showed good potential in detecting premalignant lesions and salivary LDH levels showed a marked increase which can be used as a diagnostic biomarker and serve as a potent diagnostic aid for early detection of malignancy.